Apostasy: personal rights guaranteed? - Shariffuddin, Norashikin; Mohd Padil, Hazlina; Abd Samad, Suhaimi (2022)
Apostasy is conversion from Islam to other religion and recognised as a right under the Universal Declaration of Human Rights where the rights to alter one’s faith or belief is guaranteed. However, the law relating to apostasy seems to be very strict to Muslims in Malaysia who want to alter their faith from Islam. Past studies indicated that the law in Malaysia is unfavourable for apostate to achieve their intention in renouncing from Islam although the Federal Constitution of Malaysia provides freedom for citizens to profess their preferential religion. This paper aims to explore the law relating to apostasy and its implementation against apostate who intending to renounce from Islam. This study employed a qualitative research design of a doctrinal nature using both primary and secondary data such as legislation, cases, articles and other relevant documents. It was found that despite the freedom to profess favourable religion, once a Muslim, the journey to achieve apostasy is challenging and the inconsistent rules and regulations in the States in Malaysia does not give sufficient avenue for apostate to renounce from Islam since the freedom under the Federal Constitution is not absolute.